Multi-laboratory validation of SkinEthic HCE test method for testing serious eye damage/eye irritation using liquid chemicals. (March 2016) - Alépée, N.; Leblanc, V.; Adriaens, E.; Grandidier, M.H.; Lelièvre, D.; Meloni, M.; Nardelli, L.; Roper, C.S.; Santirocco, E.; Toner, F.; Van Rompay, A.; Vinall, J.; et al.
Abstract: A prospective multicentric study of the reconstructed human corneal epithelial tissue-based in vitro test method (SkinEthic™ HCE) was conducted to evaluate its usefulness to identify chemicals as either not classified for serious eye damage/eye irritation (No Cat.) or as classified (Cat. 1/Cat. 2) within UN GHS. The aim of this study was to demonstrate the transferability and reproducibility of the SkinEthic™ HCE EITL protocol for liquids and define its predictive capacity. Briefly, 60 chemicals were three times tested (double blinded) in 3 laboratories and 45 additional chemicals were tested three times in one laboratory. Good within laboratory reproducibility was achieved of at least 88.3% (53/60) and 92.4% (97/105) for the extended data set. Furthermore, the overall concordance between the laboratories was 93.3% (56/60). The accuracy of the SkinEthic™ HCE EITL for the extended dataset, based on bootstrap resampling, was 84.4% (95% CI: 81.9% to 87.6%) with a sensitivity of 99.0% (95% CI: 96.4% to 100%) and specificity of 68.5% (95% CI: 64.0% to 74.0%), thereby meeting all acceptance criteria for predictive capacity. This efficient transferable and reproducible assay is a promising tool to be integrated within a battery of assays to perform an eye irritation risk assessment. Highlights: SkinEthic™ HCE method has been developed for the Eye Irritation Testing of Liquids. A validation study has been conducted with three laboratories on 60 substances. Good within laboratory reproducibility was achieved of at least 88.3% (53/60). The overall concordance between the laboratories was 93.3% (56/60). The accuracy was 84.4% with a sensitivity of 99.0% and specificity of 68.5% on 105 chemicals.